Reflejos de schwob en Arreola: vidas imaginarias en "nabónides" y "epitafio". - González Arce, Teresa (2012)
In Vies imaginaires (Imaginary Lifes), the French writer Marcel Schwob wrote biographies of 22 marginal characters based on the great historical narratives. Attention to the secondary details, freedom from the veracity of the facts and assimilation between life and work of the writers included in the book are some of the features of an aesthetic model that the Mexican writer Juan Jose Arreola endorses. From two texts by Arreola (“Nabonides” and “Epitafio”) and based on general considerations about the literary forms involved in the works of both writers –literary portrait and votive epigram– this article focuses this process of rewriting as an act of appropriation and self-understanding through the understanding of others